Le Corbusier : architecture et politique - Mickaël Labbé (Astérion)
Le Corbusier, certainly the most iconic representative of modern architecture, always had ambivalent connections with the political power. Although he constantly claimed that he wants to promote the idea of an everyday happiness for the people through architecture, he was in the same time trying very hard to be in the circle of power, regardless of its ideology. Through a series of paradoxes, I aim to show that Le Corbusier’s political attitude can not only be explained by historical and empirical arguments, but that it also has to be referred to a particular theoretical and philosophical conception of the nature of power. He always considered power in a purely formal and an extremely individualistic manner. Moreover, he reduced power to a simple means of efficiency in order to realize the only valuable revolution, i. e. the architectural one. Le Corbusier’s conception of power thus allies a profound reflection on the potencies of architecture and a noticeable lack of political intelligence.